Pengukuran Tingkat Kesiapan (Readiness) Mahasiswa terhadap Laboratorium Keamanan Informasi pada Teknik Informatika Universitas Pasundan - M. Ilham Saputra; Doddy Ferdiansyah (Prosiding SISFOTEK, 2019)
The need for security, especially in terms of Information Technology today is very important. Many cases of attacks using IT devices to take action criminal (cybercrime). Crimes - crimes in the cyber world occur because one of them is lack of knowledge and public awareness about current attacks. For increase science and public awareness, especially for students, the Engineering study program Informatics wants to make a facility that serves to be a means for students to do learning and exploration of knowledge about information security. Facilities to be built in the form of an Information Security laboratory, which consists of 3 types of laboratories. Construction of this facility consists of several stages, from measuring readiness to building facilities. So in this first phase of research is to measure the readiness of students against Information Security laboratory. From the research that has been done, it can be concluded that UNPAS Informatics Engineering study students are ready if this Information Security laboratory will was built.